2005
DOI: 10.1016/j.cell.2004.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Rhox: A New Homeobox Gene Cluster

Abstract: Homeobox genes encode transcription factors notable for their ability to regulate embryogenesis. Here, we report the discovery of a cluster of 12 related homeobox genes on the X chromosome expressed in male and female reproductive tissues in adult mice. These reproductive homeobox on the X chromosome (Rhox) genes are expressed in a cell type-specific manner; several are hormonally regulated, and their expression pattern during postnatal testis development corresponds to their chromosomal position. Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
361
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 219 publications
(382 citation statements)
references
References 51 publications
(11 reference statements)
14
361
2
Order By: Relevance
“…The Rhox homeobox genes are selectively expressed in male and female reproductive tissues, and thus they are likely to encode a set of transcription factors devoted to promoting and regulating gametogenesis (44). In support of this, we recently showed that mutational inactivation of Rhox5 causes aberrant germ cell apoptosis in stages V to XI of the seminiferous epithelial cycle, increased germ-cell apoptosis in stages I to IV and XII of the cycle, decreased sperm cell count, impaired sperm motility, and subfertility in mice (39). These aberrations are not the result of a germ cell defect but, rather, a Sertoli cell defect, as the Rhox5 gene and RHOX5 protein are expressed specifically in Sertoli cells within the postnatal and adult testis (38,51,59).…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…The Rhox homeobox genes are selectively expressed in male and female reproductive tissues, and thus they are likely to encode a set of transcription factors devoted to promoting and regulating gametogenesis (44). In support of this, we recently showed that mutational inactivation of Rhox5 causes aberrant germ cell apoptosis in stages V to XI of the seminiferous epithelial cycle, increased germ-cell apoptosis in stages I to IV and XII of the cycle, decreased sperm cell count, impaired sperm motility, and subfertility in mice (39). These aberrations are not the result of a germ cell defect but, rather, a Sertoli cell defect, as the Rhox5 gene and RHOX5 protein are expressed specifically in Sertoli cells within the postnatal and adult testis (38,51,59).…”
mentioning
confidence: 59%
“…1B, WT). Cells incubated without R1881 and the AR expression plasmid expressed only low levels of luciferase from the Pp reporter vector (only slightly above that of pRL-null), consistent with earlier studies showing that the Pp depends on AR and androgen for expression (3,39,51). To assess whether AR might directly regulate the Pp, we scanned the 0.6-kb Pp 5Ј flanking region for sequences conforming to consensus ARbinding sites (androgen-response elements, or AREs) (57).…”
Section: Identification Of Ares Essential For Rhox5 Pp Transcription mentioning
confidence: 79%
See 2 more Smart Citations
“…They have been shown to be expressed in both germ cells and somatic cells of reproductive tract (MacLean and Wilkinson, 2010). As most of Rhox genes are expressed on Sertoli cells which are known as "nurse" sells of the testis and have close interaction with developing germ cells, it has been deduced that Rhox genes products can regulate the expression of somatic cell gene products vital for germ cell development (Maclean et al, 2005). In addition, targeted Rhox5 knock out has resulted in increased male germ cell apoptosis and consequently reduced sperm count and fertility (Maclean et al, 2005).…”
Section: Introductionmentioning
confidence: 99%